Revisiting the Rural Superintendency: Rethinking Guiding Theories for Contemporary Practice - Erin McHenry-Sorber; Kathleen Budge (Journal of Research in Rural Education, 2018)
This conceptual article challenges researchers and practitioners to reconsider the utility of current constructs used to understand the rural school superintendency. We evaluate the rural leadership literature through two waves of scholarship: insider/outsider conceptions and place-conscious/critical place-conscious constructs. We assert critical place-conscious leadership as potentially responsive to contemporary rural realities, but we provide a number of revisions for theoretical development to increase applicability to the realities of the rural superintendency in practice in the early part of the twentyfi rst century.